A Prospective Study of Percutaneous Vertebroplasty for Chronic Painful Osteoporotic Spinal Fractures. Issue 1 (March 2013) - Zheng, Ruo-Kun; Wang, Yi-Sheng; Li, Jia-Zhen; Hao, Ying-Jie; Tan, Hong-Yu
<x xml:space="preserve">Abstract</x> Objectives To evaluate the efficacy of percutaneous vertebroplasty [PV] in patients with chronic painful osteoporotic compression fractures. Methods We performed a prospective study in which participants with unhealed, painful chronic osteoporotic vertebral fractures for at least three months [low signal in T1 and high signal in T2 on magnetic resonance imaging [MRI]], as confirmed by MRI, were prospectively assigned to undergo PV or a conservative treatment [CT]. The primary outcome was pain relief at one week, one month, three months, six months, and one year, as measured by Visual Analog Scale score. Results A total of 40 participants were enrolled and 36 [19 of 20 in the PV group and 17 of 20 in the CT group] completed the one-year follow-up [90 percent]. Changes in mean VAS score between baseline and one month was –3.7 after PV and –2.4 after CT; between baseline and six months was –3.9 after PV and –2.4 after CT; and between baseline and one year was –4.0 after PV and –2.3 after CT. The difference between groups in the reduction of mean VAS score from baseline was 1.3 [P = 0.001] at one week, 1.5 [P = 0.001] at one month, and 1.6 [P < 0.001] at one year. Conclusion PV reduced pain more effectively than did CT. It is effective in a subgroup of patients with chronic osteoporotic vertebral fracture and persistent pain. Pain relief after PV is immediate and is sustained for one year.